Incorporating multiple linear regression in analysing factors influencing consumers purchase intention for online shopping in Malaysia - Ahmad Amirul Aufa, Shakir; Noraziah, Adzhar (Semarak Ilmu Publishing, 2025)
Online shopping has become a popular method of purchasing goods and services, offering consumers the convenience of shopping from anywhere at any time, especially after the COVID-19 pandemic. Understanding the factors influencing purchase intention in an online shopping context is crucial for businesses to optimize the customer experience and increase sales. Besides, the impact of the changes that will be made by the online business based on the study result will hopefully make it easier for users to make purchasing decisions and enjoy using online services without feeling insecure about various scam activities. Therefore, this study aims to identify the factors that drive consumers' purchase intentions for online shopping in Malaysia. Using a voluntary sampling technique in the survey approach, a total of 158 respondents' data in Malaysia were selected and analyzed using multiple linear regression. Four factors were chosen in relation to purchase intention which are price, perceived usefulness, perceived ease of use, and social media. The output revealed that price, perceived usefulness, perceived ease of use, and social media have a positive significant effect on consumers’ purchase intention.